A Brief, Hospital-Initiated Motivational Interviewing and Acceptance and Commitment Therapy Intervention to Link Postpartum Mothers Who Use Illicit Drugs With Treatment and Reproductive Care: A Case Report. Issue 1 (February 2021) - Villarreal, Yolanda R.; Spellman, Mackenzie L.; Prudon, Jasmin; Northrup, Thomas F.; Berens, Pamela D.; Blackwell, Sean; Velasquez, Mary M.; Stotts, Angela L.
Abstract: Maternal substance use during the prenatal period often results in infants with compromised health outcomes. The American College of Obstetrics and Gynecology recommends screening, brief motivational interviewing, and referral to existing treatment for women who use illicit substances prenatally. However, many of these women do not present for prenatal care and are not identified as using substances until delivery of their infants, many of whom are admitted to the neonatal intensive care unit (ICU). We describe a case from a novel, hospital-initiated intervention study, Moms in ACTion (MIACT) that combines motivational interviewing (MI) and acceptance and commitment therapy (ACT) to target new mothers with an infant in the neonatal ICU who screen positive for illicit substance use prenatally or at delivery. The MIACT program consists of an adaptive intervention that includes up to three sessions. Initiation of substance use treatment and reproductive care via a gynecological visit are the primary targets of the intervention. Urine samples were collected at 2- and 6-month follow-up visits. The participant successfully completed the program, achieved both treatment outcomes, and had negative urine drug screens at follow-up visits. Improvements in readiness to change and psychological flexibility were also observed. The present case report of a new mother who used substances demonstrated feasibility for combining MI and ACT treatments and the potential for MIACT to increase treatment and contraception initiation, ultimately preventing future substance-exposed pregnancies. Highlights: Infants exposed to illicit substances (IEIS) prenatally have severe health consequences. Women who use illicit drugs prenatally (WWUIDP) often do not seek prenatal care or treatment. Hospital-initiated interventions linking WWUIDP with treatment/reproductive care may prevent future IEIS. MIACT is well suited to aid WWUIDP cope with distressing processes associated with drug use. Hospital-initiated MIACT demonstrates initial feasibility and effectiveness to link women with IEIS to treatment/reproductive care.